A novel crystalline azine-linked three-dimensional covalent organic framework for CO2 capture and conversion. Issue 83 (23rd September 2019) - Guan, Pengxin; Qiu, Jikuan; Zhao, Yuling; Wang, Huiyong; Li, Zhiyong; Shi, Yunlei; Wang, Jianji
Abstract : A novel crystalline azine-linked three-dimensional covalent organic framework was rationally synthesized and exhibited excellent performance in CO2 adsorption and conversion. Abstract : The targeted synthesis of three-dimensional covalent organic frameworks (3D COFs) is a great challenge, especially those synthesized by using a new kind of organic linkage. Herein, for the first time, a novel 3D azine-linked COF (3D-HNU5) has been synthesized and characterized. It is shown that the obtained 3D COF has a 2-fold interpenetrated diamond topology, and shows good chemical/thermal stability and a narrow pore size distribution, which exhibits excellent performance in the selective uptake of CO2 over N2 . Moreover, the 3D-HNU5 is found to be an efficient catalyst for the cycloaddition of propargylic alcohols with CO2 into carbonates with excellent catalytic activity under mild conditions.